Chemoselective dithioacetalization of aldehydes using silica sulfuric acid as a reusable catalyst - Pore, D. M.; Desai, Uday V.; Mane, R. B.; Wadgaonkar, P. P. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2006)
Silica sulfuric acid has been found to be an efficient and reusable catalyst for chemoselective dithioacetalization of aldehydes over ketones, in excellent yields.
Keywords: Chemoselective; dithioacetalization; silica sulfuric acid

Potassium phosphate or silica sulfuric acid catalyzed conjugate addition of thiols to alpha,beta-unsaturated ketones at room temperature under solvent-free conditions - Pore, D. M.; Soudagar, M. S.; Desai, Uday V.; Thopate, T. S.; Wadagaonkar, P. P. (Tetrahedron Letters, 2006)
Potassium phosphate and silica sulfuric acid have been found to be useful and highly efficient catalysts for conjugate addition of thiols to alpha,beta-unsaturated ketones under solvent-free conditions, at room temperature. Silica sulfuric acid (SSA) was found to be suitable for electron-deficient enones while potassium phosphate was found to effect thia-Michael addition with both, electron-deficient as well as electron-rich conjugated ketones. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: alpha; beta-unsaturated ketones; chalcones; conjugated enones; Michael addition; Potassium phosphate; silica sulfuric acid; thiols